Monatomic nitrogen-doped carbon catalysts, preparation and use thereof

CN122273563BActive Publication Date: 2026-11-03DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610739573.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-27
Publication Date
2026-11-03
Estimated Expiration
2046-05-27

AI Technical Summary

Technical Problem

然而,这些方法存在一些不足之处,如卤醇法会产生大量含卤废水;有机过氧化物氧化法存在过氧化物储存和运输不安全,且反应选择性较低等问题

Benefits of technology

1.高活性和高选择性:本发明的单原子氮掺杂碳催化剂具有独特的电子结构和高原子利用率,由于复合结构的构建,可使NC上的N原子向VN中的V原子转移电子,使NC上的N原子具有亲电性,从而优化了对含氧中间体的吸附。能够在温和的反应条件下高效催化环己烯环氧化反应,环氧环己烷的选择性和收率均较高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of heterogeneous catalysts, and provides a single-atom nitrogen-doped carbon catalyst and a preparation and application thereof.Ammonium metavanadate is dissolved in hot water, melamine is added to the obtained solution, the powder is obtained by stirring and evaporating water, the obtained powder is collected, grinding is performed to make the particle size of the powder less than or equal to 50 microns, and the nitrogen-doped carbon material VN@NC carrier is obtained after calcination; the nitrogen-doped carbon material is weighed and dispersed in a methanol and / or aqueous solution, an aqueous metal salt solution is added, stirring is performed at room temperature after dispersion, and centrifugal drying is performed; the obtained solid is pyrolyzed for 1-5 hours to obtain a single-atom nitrogen-doped carbon catalyst.The application solves the problems of the organic peroxide oxidation method, such as unsafe storage and transportation of peroxide and low reaction selectivity.The catalyst has high activity, high selectivity and good stability, and can be used for efficiently catalyzing the epoxidation reaction of cyclohexene to prepare epoxycyclohexane under mild reaction conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heterogeneous catalyst technology, and particularly relates to a single-atom nitrogen-doped carbon catalyst and its preparation and application. Background Technology

[0002] Cyclohexane oxide is an important organic chemical intermediate widely used in fragrances, pharmaceuticals, and polymer materials. Currently, the main production methods for cyclohexane oxide include the traditional halohydrin process and the organic peroxide oxidation process. However, these methods have some drawbacks. For example, the halohydrin process generates large amounts of halogen-containing wastewater; the organic peroxide oxidation process suffers from problems such as unsafe storage and transportation of peroxides and low reaction selectivity.

[0003] Therefore, developing a highly efficient and environmentally friendly cyclohexene epoxidation catalyst is of significant practical importance. In recent years, single-atom catalysts have demonstrated enormous potential in the field of catalysis due to their unique electronic structure and high atom utilization. Nitrogen-doped carbon materials possess excellent chemical stability and electronic conductivity, making it promising to prepare high-performance cyclohexene epoxidation catalysts by loading single atoms onto them.

[0004] This invention designs a core@shell VN@NC carrier using a simple physical mixing and calcination process. During carrier construction, VN nanoparticles are embedded and uniformly distributed within the NC framework. Due to the composite structure, N atoms on the NC can transfer electrons to V atoms in the VN, making the N atoms on the NC electrophilic and thus optimizing the adsorption of oxygen-containing intermediates. Summary of the Invention

[0005] The purpose of this invention is to provide a single-atom nitrogen-doped carbon catalyst and its preparation and application. This catalyst has high activity, high selectivity and good stability, and can efficiently catalyze the epoxidation reaction of cyclohexene to prepare cyclohexane oxide under mild reaction conditions.

[0006] The technical solution adopted in this invention is described in detail below.

[0007] A single-atom nitrogen-doped carbon catalyst for the epoxidation of cyclohexene to prepare cyclohexane oxide and its preparation method thereof, specifically including the following steps: In a first aspect, a method for preparing a single-atom nitrogen-doped carbon catalyst includes the following steps: S1: Dissolve ammonium metavanadate in hot water at 80~95℃ to obtain a solution; add melamine to the obtained solution and stir at 70~100℃ (preferably 75~95℃, more preferably 80~90℃) to evaporate the water and obtain a powder; the mass ratio of ammonium metavanadate to melamine is 1:10~1:40 (preferably 1:15~1:35, more preferably 1:20~1:30). S2: Collect the powder obtained in step S1, grind it to make the powder particle size less than or equal to 50 micrometers (preferably 40 micrometers, more preferably 30 micrometers), and calcine it at a temperature of 500~600℃ (preferably 520~580℃, more preferably 550~560℃) for 2~6 hours (preferably 2.5~4.5h, more preferably 3~4h) to obtain nitrogen-doped carbon material VN@NC carrier; S3: Weigh the above nitrogen-doped carbon material and disperse it in an aqueous solution. Add an aqueous solution of metal salt, and stir the mixture at room temperature after dispersion. Centrifuge the mixture to obtain a solid, wash it, and dry it. S4: Weigh the solid obtained in step S3 and pyrolyze it at 800~1000℃ (preferably 830~980℃, more preferably 850~950℃) and in an inert atmosphere for 1~5 hours (preferably 1.5~4h, more preferably 2~3h) to obtain a single-atom nitrogen-doped carbon catalyst.

[0008] Furthermore, the stirring time in step S1 is 10 to 20 hours (preferably 12 to 18 hours, more preferably 14 to 16 hours). In step S2, the heating rate from room temperature to the calcination temperature is 2~10℃ / min, and the atmosphere is an inert atmosphere, preferably a nitrogen and / or argon atmosphere.

[0009] Furthermore, in step S3, the concentration of the nitrogen-doped carbon material in the aqueous solution is 0.01-0.2 g / mL (preferably 0.03-0.16 g / mL, more preferably 0.05-0.15 g / mL); The concentration of the aqueous solution of the metal salt is 100~120 mg / mL; The metal salt is one or more of copper nitrate, copper chloride, ferric nitrate, ferric chloride, cobalt nitrate, and cobalt chloride; The mass ratio of the metal salt to the VN@NC carrier is 1:100 to 1:10 (preferably 1:80 to 1:30, more preferably 1:50 to 1:40). The stirring time is 5-10 hours (preferably 6-9 hours, more preferably 7-8 hours), the drying temperature is 60-90℃, and the drying time is 10-24 hours; The ultrasonic dispersion is ultrasonic dispersion.

[0010] Furthermore, in step S4, the heating rate from room temperature to the pyrolysis temperature is 2~10℃ / min, and the inert atmosphere is nitrogen and / or argon.

[0011] Secondly, the single-atom nitrogen-doped carbon catalyst prepared by the aforementioned preparation method.

[0012] Thirdly, the application of catalysts in the catalytic epoxidation of cyclohexene to prepare cyclohexane oxide.

[0013] Furthermore, the reaction is carried out in a reaction vessel, where the single-atom nitrogen-doped carbon catalyst, solvent, and reactant cyclohexene are added to the reaction vessel, the air inside the vessel is replaced with oxygen, oxygen is added to the reaction pressure, and the epoxidation reaction is completed at the reaction temperature to obtain the cyclohexane oxide.

[0014] Furthermore, the mass ratio of catalyst to cyclohexene is 1:200 to 1:100 (preferably 1:200 to 1:120, more preferably 1:200 to 1:150), and the mass ratio of solvent to cyclohexene is 1:1 to 2:1 (preferably 1.2:1 to 1.8:1, more preferably 1.3:1 to 1.6:1).

[0015] Furthermore, the solvent is one or more of acetonitrile, dichloromethane, dichloroethane, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and 1,4-dioxane.

[0016] Furthermore, the reaction pressure is 0.5~2MPa (preferably 1~2MPa, more preferably 1.3~1.8MPa), the reaction temperature is 50~80℃ (preferably 55~75℃, more preferably 60~70℃), and the reaction time is 2~5 hours (preferably 2.5~4.5h, more preferably 3~4h).

[0017] Beneficial effects 1. High activity and high selectivity: The single-atom nitrogen-doped carbon catalyst of this invention possesses a unique electronic structure and high atom utilization. Due to the construction of the composite structure, electrons can be transferred from the N atom on NC to the V atom in VN, making the N atom on NC electrophilic, thereby optimizing the adsorption of oxygen-containing intermediates. It can efficiently catalyze the epoxidation reaction of cyclohexene under mild reaction conditions, with high selectivity and yield of cyclohexane oxide.

[0018] 2. Good stability: The single-atom active centers in the catalyst are uniformly dispersed on the nitrogen-doped carbon support, exhibiting good stability, not easily agglomerating or being lost, and can be reused multiple times.

[0019] 3. Environmentally friendly and pollution-free: This invention uses oxygen as an oxidant, and no pollutants such as halogen-containing wastewater are generated during the reaction process, which meets the requirements of green chemistry. Detailed Implementation

[0020] The present application will be further explained below with reference to the embodiments. The characterization methods used in the following embodiments are as follows: particle size and particle size distribution were measured by field emission scanning electron microscopy (FESEM); crystal form and impurity phases were measured by X-ray diffraction (XRD); elemental content was measured by X-ray photoelectron spectroscopy (XPS); single-atom dispersion was measured by aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (AC-HAADF-STEM) combined with energy dispersive spectroscopy (EDS); mixing homogeneity was measured by surface scanning analysis of energy dispersive spectroscopy (EDS); specific surface area and pore structure were measured by nitrogen adsorption-desorption (BET); nitrogen doping amount was measured by elemental analysis; and metal content was measured by inductively coupled plasma atomic emission spectrometry (ICP).

[0021] Example 1: Preparation of catalyst Cu-VN@NC S1: Dissolve 0.3g of ammonium metavanadate in 60mL of 90℃ deionized water until completely dissolved, add 6g of melamine (mass ratio of ammonium metavanadate to melamine 1:20), stir at 90℃ for 14h until the water evaporates, and obtain powder; S2: Collect the powder and grind it thoroughly to ensure the particle size is less than or equal to 50 micrometers. Mix the two precursors thoroughly and evenly. Calcine the mixture in a tube furnace under a nitrogen atmosphere from room temperature to 560℃ at a rate of 6℃ / min for 3 hours to obtain the VN@NC support, where VN refers to vanadium nitride and NC refers to nitrogen-doped carbon. XPS analysis showed that the N content in the support was 66.8 wt% and the V content was 1.5 wt%. FESEM observation showed that the VN particles had a uniform size distribution of 15-25 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 250 m². 2 / g, with a pore size range of 5~8nm, proving that the carbon framework is rich in pores; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 120μL of 100mg / mL copper nitrate aqueous solution (copper nitrate metal salt to carrier mass ratio 1:50), sonicate for 30min, stir at room temperature for 7h, centrifuge and wash, and then vacuum dry at 70℃ for 14h. S4: The solid obtained in step S3 was heated from room temperature to 950℃ at a rate of 5℃ / min in an argon atmosphere and pyrolyzed for 2 hours to obtain a single-atom nitrogen-doped carbon catalyst Cu-VN@NC. AC-HAADF-STEM testing revealed isolated Cu atom bright spots, with no Cu nanoparticles present, confirming single-atom dispersion. ICP testing showed a Cu elemental loading of 0.63wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the support surface.

[0022] Example 2 Preparation of catalyst Co-Fe-VN@NC S1: Dissolve 0.25g of ammonium metavanadate in 55mL of 80℃ deionized water until completely dissolved, add 5g of melamine (mass ratio of ammonium metavanadate to melamine 1:20), stir at 85℃ for 16h until the water evaporates; S2: Collect the powder and grind it thoroughly to ensure the particle size is less than or equal to 50 micrometers. Mix the two precursors thoroughly and evenly. Calcine the mixture in a tube furnace under a nitrogen atmosphere from room temperature to 530℃ at a rate of 4℃ / min for 4 hours to obtain the VN@NC support. XPS analysis showed that the N content in the support was 66.9 wt% and the V content was 1.7 wt%. FESEM observation showed that the VN particles had a uniform size distribution of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. The specific surface area of ​​the support reached 229 m² / s². 2 / g, with a pore size range of 5~8nm, proving that the carbon framework is rich in pores; S3: Take 0.5g of VN@NC and place it in 10mL of methanol for ultrasonic dispersion. Add 100μL of 100mg / mL cobalt chloride aqueous solution (cobalt chloride metal salt to carrier mass ratio 1:50), sonicate for 25min, stir at room temperature for 6h, centrifuge and wash, and then vacuum dry at 65℃ for 16h. S4: The solid obtained in step S3 was heated from room temperature to 900℃ at a rate of 5℃ / min in an argon atmosphere and pyrolyzed for 3 hours to obtain a single-atom nitrogen-doped carbon catalyst Co-VN@NC. AC-HAADF-STEM testing revealed isolated Co atom bright spots, with no Co nanoparticles present, confirming single-atom dispersion. ICP testing showed a Co element loading of 0.65wt%, and EDS surface scanning showed that Co single atoms were uniformly distributed on the support surface.

[0023] Example 3 Preparation of catalyst Fe-VN@NC S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 85℃ deionized water until completely dissolved, add 8g of melamine (mass ratio of ammonium metavanadate to melamine 1:40), stir at 70℃ for 20h until the water evaporates; S2: Collect the powder and grind it thoroughly to ensure the particle size is less than or equal to 50 micrometers. Mix the two precursors thoroughly and evenly. Calcine the mixture in a tube furnace under a nitrogen atmosphere from room temperature to 600℃ at a rate of 10℃ / min for 2 hours to obtain the VN@NC support. XPS analysis showed that the N content in the support was 68.3 wt% and the V content was 1.1 wt%. FESEM observation showed that the VN particles had a uniform size distribution of 20-30 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. The specific surface area of ​​the support reached 248 m² / s². 2 / g, with a pore size range of 4~6nm, proving that the carbon framework is rich in pores; S3: Take 0.5g of VN@NC and disperse it in 10mL of methanol by ultrasonication. Add 50μL of 100mg / mL ferric nitrate aqueous solution (ferric nitrate metal salt to carrier mass ratio 1:100), sonicate for 20min, stir at room temperature for 10h, centrifuge and wash, and then vacuum dry at 90℃ for 10h. S4: The solid obtained in step S3 was heated from room temperature to 800℃ at a rate of 5℃ / min in an argon atmosphere and pyrolyzed for 5 h to obtain a single-atom nitrogen-doped carbon catalyst Fe-VN@NC. AC-HAADF-STEM testing revealed isolated Fe atom bright spots, with no Fe nanoparticles present, confirming single-atom dispersion. ICP testing showed an Fe elemental loading of 0.32 wt%, and EDS surface scanning showed that Fe single atoms were uniformly distributed on the support surface.

[0024] Example 4 Preparation of catalyst Cu-VN@NC-41 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 80℃ deionized water until completely dissolved, add 3g of melamine (mass ratio of ammonium metavanadate to melamine 1:15), stir at 80℃ for 12h until the water evaporates; S2-S4: The process and conditions were the same as in Examples 1 S2-S4, yielding the catalyst Cu-VN@NC-41. XPS analysis showed that the N content in the VN@NC-41 support was 66.7 wt% and the V content was 2.2 wt%. FESEM observation showed that the VN particles had a particle size of 20 nm, with uniform particle size distribution and no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 246 m². 2 / g, with a pore size range of 5~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing revealed isolated Cu atom bright spots with no Cu nanoparticles, confirming that the distribution was single-atom dispersion. ICP testing showed that the Cu element loading was 0.61 wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the support surface.

[0025] Example 5 Preparation of catalyst Cu-VN@NC-42 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 80℃ deionized water until completely dissolved, add 5g of melamine (mass ratio of ammonium metavanadate to melamine 1:25), stir at 80℃ for 12h until the water evaporates; S2-S4: The process and conditions were the same as in Examples 1 S2-S4, yielding the catalyst Cu-VN@NC-41. XPS analysis showed that the N content in the support VN@NC-42 was 66.8 wt% and the V content was 2.2 wt%. FESEM observation showed that the VN particles had a particle size of 20 nm, with uniform particle size distribution and no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 248 m². 2 / g, with a pore size range of 4~7nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Cu atom bright spots, with no Cu nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Cu element loading was 0.60wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the support surface.

[0026] Example 6 Preparation of catalyst Cu-VN@NC-43 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 80℃ deionized water until completely dissolved, add 7g of melamine (mass ratio of ammonium metavanadate to melamine 1:35), and stir at 80℃ for 12h until the water evaporates; S2-S4: The process and conditions were the same as in Examples 1 S2-S4, yielding the catalyst Cu-VN@NC-43. XPS analysis showed that the N content in the VN@NC-43 support was 68.9 wt% and the V content was 1.6 wt%. FESEM observation showed that the VN particles had a uniform size of 15-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 243 m². 2 / g, with a pore size range of 6~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Cu atom bright spots, with no Cu nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Cu element loading was 0.58wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the support surface.

[0027] Example 7 Preparation of catalyst Cu-VN@NC-51 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 80℃ deionized water until completely dissolved, add 4g of melamine (mass ratio of ammonium metavanadate to melamine 1:20), stir at 85℃ for 12h until the water evaporates; S2-S4: The process and conditions were the same as in Examples 1 S2-S4, yielding the catalyst Cu-VN@NC-51. XPS analysis showed that the N content in the VN@NC-51 support was 66.5 wt% and the V content was 2.1 wt%. FESEM observation showed that the VN particles had a uniform size of 20-30 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. The specific surface area of ​​the support reached 238 m², as determined by nitrogen adsorption-desorption (BET). 2 / g, with a pore size range of 4~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Cu atom bright spots, with no Cu nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Cu element loading was 0.59wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the support surface.

[0028] Example 8 Preparation of catalyst Fe-VN@NC-52 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 90℃ deionized water until completely dissolved, add 4g of melamine (mass ratio of ammonium metavanadate to melamine 1:20), stir at 90℃ for 14h until the water evaporates; S2-S4: The process and conditions were the same as in Examples 3 S2-S4, yielding the catalyst Fe-VN@NC-52. XPS analysis showed that the N content in the support VN@NC-52 was 67.6 wt% and the V content was 2.2 wt%. FESEM observation showed that the VN particles had a uniform size of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 248 m². 2 / g, pore size range of 5~9nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM test observed isolated Fe atom bright spots, no Fe nanoparticles appeared, proving that it is a single atom dispersion; ICP test showed that the Fe element loading was 0.58wt%, and EDS surface scan showed that Fe single atoms were uniformly distributed on the surface of the support.

[0029] Example 9 Preparation of catalyst Co-VN@NC-53 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 81℃ hot deionized water until completely dissolved, add 4g of melamine (mass ratio of ammonium metavanadate to melamine 1:20), stir at 75℃ for 18h until water evaporates; S2-S4: Process and conditions were simultaneously applied in Example 2 S2-S4 to obtain the catalyst Co-VN@NC-53. XPS analysis showed that the N content in the VN@NC-53 support was 67.8 wt% and the V content was 2.0 wt%. FESEM observation showed that the VN particle size was 10-20 nm, with uniform particle size distribution and no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 245 m². 2 / g, with a pore size range of 5~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Co atom bright spots, with no Co nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Co element loading was 0.60wt%, and EDS surface scanning showed that Co single atoms were uniformly distributed on the support surface.

[0030] Example 10 Preparation of catalyst Cu-VN@NC-61 S1: The process and conditions are the same as S1 in Example 1; S2: After grinding the powder to a particle size of less than 50 μm, the temperature was increased from room temperature to 550℃ at a rate of 5℃ / min in a tube furnace under nitrogen atmosphere, and calcined for 3 hours to obtain the VN@NC support. XPS analysis showed that the N content in the support VN@NC-61 was 66.9 wt% and the V content was 1.8 wt%. FESEM observation showed that the VN particles had a particle size of 15-20 nm, with uniform particle size distribution and no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. The specific surface area of ​​the support reached 244 m², as determined by nitrogen adsorption-desorption (BET) analysis. 2 / g, with a pore size range of 4~7nm, indicating abundant porosity in the carbon framework; S3-S4: The process and conditions were the same as S3-S4 in Example 1, and the catalyst Cu-VN@NC-61 was obtained. AC-HAADF-STEM testing showed isolated Cu atom bright spots and no Cu nanoparticles, which proved that it was a single-atom dispersion. ICP testing showed that the Cu element loading was 0.61wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the surface of the support.

[0031] Example 11 Preparation of catalyst Fe-VN@NC-62 S1: The process and conditions are the same as S1 in Example 3; S2: After grinding the powder to a particle size of less than 50 μm, the temperature was increased from room temperature to 520 °C at a rate of 6 °C / min in a tube furnace under nitrogen atmosphere and calcined for 4 h to obtain the VN@NC support. XPS analysis showed that the N content in the support VN@NC-62 was 66.9 wt% and the V content was 2.0 wt%. FESEM observation showed that the VN particles had a particle size of 10-20 nm, with uniform particle size distribution and no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. The specific surface area of ​​the support reached 250 m² / s², as determined by nitrogen adsorption-desorption (BET) analysis. 2 / g, with a pore size range of 5~9nm, proving that the carbon framework is rich in pores; S3-S4: The process and conditions were the same as in S3-S4 of Example 3, and the catalyst Fe-VN@NC-62 was obtained. The AC-HAADF-STEM test showed isolated Fe atom bright spots and no Fe nanoparticles, which proved that it was a single atom dispersion. The ICP test showed that the Fe element loading was 0.60 wt%, and the EDS surface scan showed that the Fe single atoms were uniformly distributed on the surface of the support.

[0032] Example 12 Preparation of catalyst Co-VN@NC-63 S1: The process and conditions are the same as S1 in Example 2; S2: After grinding the powder to a particle size of less than 50 μm, the temperature was increased from room temperature to 580℃ at a rate of 8℃ / min in a tube furnace under nitrogen atmosphere, and calcined for 2 hours to obtain the VN@NC support. XPS analysis showed that the N content in the support VN@NC-63 was 67.8 wt% and the V content was 2.1 wt%. FESEM observation showed that the VN particles had a particle size of 10-15 nm, with uniform particle size distribution and no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. The specific surface area of ​​the support reached 245 m² / s². 2 / g, with a pore size range of 4~7nm, proving that the carbon framework is rich in pores; S3-S4: The process and conditions were the same as S3-S4 in Example 2, and the catalyst Co-VN@NC-63 was obtained. AC-HAADF-STEM testing showed isolated Co atom bright spots and no Co nanoparticles, which proved that it was a single-atom dispersion. ICP testing showed that the Co element loading was 0.58wt%, and EDS surface scanning showed that Co single atoms were uniformly distributed on the surface of the support.

[0033] Example 13 Preparation of catalyst Cu-VN@NC-71 S1-S2: The process and conditions are the same as S1-S2 in Example 1. S3: Disperse 0.5g of VN@NC in 10mL of methanol by ultrasonication, add 100μL of 100mg / mL copper chloride aqueous solution (copper chloride metal salt to carrier mass ratio 1:50), sonicate for 30min, stir at room temperature for 7h, centrifuge and wash, and then vacuum dry at 70℃ for 14h; S4: The process and conditions were the same as in S4 of Example 1, yielding the catalyst Cu-VN@NC-71. XPS analysis showed that the N content in the VN@NC-71 support was 66.8 wt% and the V content was 1.9 wt%. FESEM observation revealed that the VN particles had a uniform size of 15-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 249 m². 2 / g, with a pore size range of 4~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Cu atom bright spots, with no Cu nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Cu element loading was 0.57wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the support surface.

[0034] Example 14 Preparation of catalyst Fe-VN@NC-72 S1-S2: The process and conditions are the same as S1-S2 in Example 3. S3: Take 0.5g of VN@NC and place it in 10mL of methanol for ultrasonic dispersion. Add 100μL of 100mg / mL ferric chloride aqueous solution (ferric chloride metal salt to carrier mass ratio 1:50), sonicate for 20min, stir at room temperature for 10h, centrifuge and wash, and then vacuum dry at 90℃ for 10h. S4: The process and conditions were the same as in Example 3, S4, to obtain the catalyst Fe-VN@NC-72. XPS analysis showed that the N content in the VN@NC-72 support was 67.1 wt% and the V content was 2.1 wt%. FESEM observation showed that the VN particles had a uniform size of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 246 m². 2 / g, with a pore size range of 5~7nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Fe atom bright spots, with no Fe nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Fe element loading was 0.61wt%, and EDS surface scanning showed that Fe single atoms were uniformly distributed on the support surface.

[0035] Example 15 Preparation of catalyst Co-Cu-VN@NC-73 S1-S2: The process and conditions are the same as S1-S2 in Example 2. S3: Take 0.5g of VN@NC and place it in 10mL of methanol for ultrasonic dispersion. Add 100μL of 100mg / mL cobalt nitrate-copper chloride mixed aqueous solution (mass ratio of 1:1, mass ratio of cobalt chloride, copper chloride metal salt to carrier 1:50), sonicate for 25min, stir at room temperature for 6h, centrifuge and wash, and then vacuum dry at 65℃ for 16h. S4: The process and conditions were the same as in S4 of Example 2, yielding the catalyst Co-Cu-VN@NC-73. XPS analysis showed that the N content in the VN@NC-73 support was 67.0 wt% and the V content was 2.0 wt%. FESEM observation showed that the VN particles had a uniform size of 20-25 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 249 m². 2 / g, with a pore size range of 5~9nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Co atom bright spots, with no Co nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Co element loading was 0.59wt%, and EDS surface scanning showed that Co single atoms were uniformly distributed on the support surface.

[0036] Example 16 Preparation of catalyst Cu-VN@NC-81 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Disperse 0.6g of VN@NC in 12mL of methanol by ultrasonication, add 100μL of 100mg / mL copper nitrate aqueous solution (copper nitrate metal salt to carrier mass ratio 1:60), sonicate for 30min, stir at room temperature for 7h, centrifuge and wash, and then vacuum dry at 70℃ for 14h; S4: The process and conditions were the same as in S4 of Example 1, yielding the catalyst Cu-Cu-VN@NC-81. XPS analysis showed that the N content in the VN@NC-81 support was 66.8 wt% and the V content was 1.8 wt%. FESEM observation revealed that the VN particles had a uniform size of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 246 m². 2 / g, with a pore size range of 4~9nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Cu atom bright spots, with no Cu nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Cu element loading was 0.61wt%, and EDS surface scanning showed that Cu single atoms were uniformly distributed on the support surface.

[0037] Example 17 Preparation of catalyst Fe-VN@NC-82 S1-S2: The process and conditions are the same as S1-S2 in Example 3; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 200μL of 100mg / mL ferric nitrate aqueous solution (ferric nitrate metal salt to carrier mass ratio 1:30), sonicate for 20min, stir at room temperature for 10h, centrifuge and wash, and then vacuum dry at 90℃ for 10h. S4: The process and conditions were the same as in Example 3, S4, to obtain the catalyst Fe-VN@NC-82. XPS analysis showed that the N content in the VN@NC-82 support was 66.6 wt% and the V content was 2.1 wt%. FESEM observation showed that the VN particles had a uniform size of 15-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 245 m². 2 / g, with a pore size range of 5~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Fe atom bright spots, with no Fe nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Fe element loading was 0.63wt%, and EDS surface scanning showed that Fe atoms were uniformly distributed on the support surface.

[0038] Example 18 Preparation of catalyst Co-VN@NC-83 S1-S2: The process and conditions are the same as S1-S2 in Example 2; S3: Take 0.5g of VN@NC and place it in 10mL of methanol for ultrasonic dispersion. Add 250μL of 100mg / mL cobalt nitrate aqueous solution (cobalt nitrate metal salt to carrier mass ratio 1:20), sonicate for 25min, stir at room temperature for 6h, centrifuge and wash, and then vacuum dry at 65℃ for 16h. S4: The process and conditions were the same as in S4 of Example 2, yielding the catalyst Co-VN@NC-83. XPS analysis showed that the N content in the VN@NC-83 support was 67.2 wt% and the V content was 1.9 wt%. FESEM observation revealed that the VN particles had a uniform size of 10-15 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 243 m². 2 / g, with a pore size range of 5~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Co atom bright spots, with no Co nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Co element loading was 0.60wt%, and EDS surface scanning showed that Co atoms were uniformly distributed on the support surface.

[0039] Example 19 Preparation of catalyst Cu-VN@NC-91 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 120μL of 100mg / mL copper nitrate aqueous solution (copper nitrate metal salt to carrier mass ratio 1:50). After ultrasonication for 30min, stir at room temperature for 6h. After centrifugation and washing, dry under vacuum at 70℃ for 12h. S4: The process and conditions were the same as in S4 of Example 1, yielding the catalyst Cu-VN@NC-91. XPS analysis showed that the N content in the VN@NC-91 support was 67.0 wt% and the V content was 1.9 wt%. FESEM observation revealed that the VN particles had a uniform size of 10-15 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 248 m². 2 / g, with a pore size range of 5~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Cu atom bright spots, with no Cu nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Cu element loading was 0.58wt%, and EDS surface scanning showed that Cu atoms were uniformly distributed on the support surface.

[0040] Example 20 Preparation of catalyst Fe-VN@NC-92 S1-S2: The process and conditions are the same as S1-S2 in Example 3. S3: Take 0.5g of VN@NC and place it in 10mL of methanol for ultrasonic dispersion. Add 50μL of 100mg / mL ferric nitrate aqueous solution (ferric nitrate metal salt to carrier mass ratio 1:100). After ultrasonication for 20min, stir at room temperature for 8h. After centrifugation and washing, dry under vacuum at 80℃ for 16h. S4: The process and conditions were the same as in S4 of Example 3, yielding the catalyst Fe-VN@NC-92. XPS analysis showed that the N content in the VN@NC-92 support was 66.4 wt% and the V content was 2.0 wt%. FESEM observation revealed that the VN particles had a uniform size of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 246 m². 2 / g, with a pore size range of 4~9nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Fe atom bright spots, with no Fe nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Fe element loading was 0.61wt%, and EDS surface scanning showed that Fe atoms were uniformly distributed on the support surface.

[0041] Example 21 Preparation of catalyst Co-VN@NC-93 S1-S2: The process and conditions are the same as S1-S2 in Example 2; S3: Take 0.5g of VN@NC and place it in 10mL of methanol for ultrasonic dispersion. Add 100μL of 100mg / mL cobalt chloride aqueous solution (cobalt chloride metal salt to carrier mass ratio 1:50). After ultrasonication for 25min, stir at room temperature for 10h. After centrifugation and washing, dry under vacuum at 60℃ for 24h. S4: The process and conditions were the same as in S4 of Example 2, yielding the catalyst Co-VN@NC-93. XPS analysis showed that the N content in the VN@NC-93 support was 66.8 wt% and the V content was 2.0 wt%. FESEM observation revealed that the VN particles had a uniform size of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed without local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 247 m². 2 / g, with a pore size range of 5~9nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Co atom bright spots, with no Co nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Co element loading was 0.62wt%, and EDS surface scanning showed that Co atoms were uniformly distributed on the support surface.

[0042] Example 22 Preparation of catalyst Cu-VN@NC-101 S1-S3: The process and conditions are the same as in Example 1, S1-S3; S4: The solid obtained in step S3 was pyrolyzed at 900℃ for 3 hours under an argon atmosphere by heating at 5℃ / min to obtain the catalyst Co-VN@NC-93. XPS analysis showed that the N content in the support VN@NC-101 was 66.6 wt% and the V content was 2.1 wt%. FESEM observation showed that the VN particles had a uniform size distribution of 15-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 250 m². 2 / g, with a pore size range of 5~9nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Cu atom bright spots, with no Cu nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Cu element loading was 0.60wt%, and EDS surface scanning showed that Cu atoms were uniformly distributed on the support surface.

[0043] Example 23 Preparation of catalyst Fe-VN@NC-102 S1-S3: The process and conditions are the same as in Example 3S1-S3; S4: The solid obtained in step S3 was heated to 900℃ in an argon atmosphere at a rate of 5℃ / min and pyrolyzed for 3 hours to obtain the catalyst Fe-VN@NC-102. XPS analysis showed that the N content in the support VN@NC-102 was 66.8 wt% and the V content was 2.0 wt%. FESEM observation showed that the VN particles had a uniform size of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 246 m². 2 / g, with a pore size range of 4~8nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Fe atom bright spots, with no Fe nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Fe element loading was 0.57wt%, and EDS surface scanning showed that Fe atoms were uniformly distributed on the support surface.

[0044] Example 24 Preparation of catalyst Co-VN@NC-103 S1-S3: The process and conditions are the same as in Example 2, S1-S3; S4: The solid obtained in step S3 was heated to 850℃ at a rate of 5℃ / min under an argon atmosphere and pyrolyzed for 4 hours to obtain the catalyst Co-VN@NC-103. XPS analysis showed that the N content in the VN@NC-103 support was 66.3 wt% and the V content was 1.8 wt%. FESEM observation showed that the VN particles had a uniform size of 10-20 nm with no obvious agglomeration. EDS surface scan analysis showed that V, N, and C elements were uniformly distributed with no local enrichment. Nitrogen adsorption-desorption (BET) analysis showed that the specific surface area of ​​the support reached 249 m². 2 / g, with a pore size range of 5~9nm, proving that the carbon framework is rich in pores; AC-HAADF-STEM testing showed isolated Co atom bright spots, with no Co nanoparticles appearing, proving that it is a single-atom dispersion; ICP testing showed that the Co element loading was 0.59wt%, and EDS surface scanning showed that Co atoms were uniformly distributed on the support surface.

[0045] Example 25 0.1 g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene (solvent:cyclohexene = 1.5:1). The air in the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 92.3% and the selectivity of cyclohexane oxide was 97.9%.

[0046] Example 26 0.133 g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 40 g of acetonitrile and 20 g of cyclohexene (solvent:cyclohexene = 2:1). The air in the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 93.8% and the selectivity of cyclohexane oxide was 97.5%.

[0047] Example 27 0.2 g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 20 g of acetonitrile and 20 g of cyclohexene (solvent:cyclohexene = 1:1). The air in the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 94.1% and the selectivity of cyclohexane oxide was 96.8%.

[0048] Example 28 0.1g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 30g of dichloromethane and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 91.8% and the selectivity of cyclohexane oxide was 97.6% by chromatography.

[0049] Example 29 0.1g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reaction vessel, followed by the addition of 15g acetonitrile, 15g dichloromethane, and 20g cyclohexene. The air in the vessel was replaced with oxygen three times, and the oxygen pressure was increased to 1.5MPa. The reaction vessel was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 93.2% and the selectivity of cyclohexane oxide was 98.1%.

[0050] Example 30 0.1 g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 30 g of 1,4-dioxane and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 90.7% and the selectivity of cyclohexane oxide was 96.9%.

[0051] Example 31 0.1g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reaction vessel, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the vessel was replaced with oxygen three times, and the oxygen was purged to 1MPa. The reaction vessel was sealed and stirred at 65°C for 4 hours. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 90.9% and the selectivity of cyclohexane oxide was 97.2% by chromatography.

[0052] Example 32 0.1g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air inside the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 70°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 93.6% and the cyclohexane oxide selectivity was 94.3%.

[0053] Example 33 0.1g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 0.8MPa. The reactor was then sealed and stirred at 55°C for 5 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 89.7% and the selectivity of cyclohexane oxide was 98.3%.

[0054] Example 34 0.1 g of the VN@NC catalyst prepared in Example 1 was weighed into a reactor. Then, 30 g of acetonitrile and 20 g of cyclohexene were added. The air in the reactor was replaced three times with oxygen, and the pressure was increased to 1.5 MPa. The reactor was sealed and stirred at 60°C for 3 hours. After the reaction, the reaction solution was filtered, and the oil phase was analyzed by chromatography. The cyclohexene conversion rate was 92.5%, the selectivity for cyclohexane oxide was 97.8%, and the purity of cyclohexane oxide after distillation was 99.6%. A recycling experiment was conducted on the solid catalyst (process and conditions as above), and the results are shown in the table below.

[0055] Example 35 Weigh 0.1g of the Co-VN@NC catalyst prepared in Example 2 into a reactor, then add 30g of acetonitrile and 20g of cyclohexene. Replace the air in the reactor with oxygen three times, and purge with oxygen to 1.5MPa. Seal the reactor and stir at 60°C for 3 hours. After the reaction is complete, filter the reaction solution. Chromatographic analysis showed that the cyclohexene conversion rate was 91.5% and the selectivity of cyclohexane oxide was 97.2%.

[0056] Example 36 0.1g of the Fe-VN@NC catalyst prepared in Example 3 was weighed into a reaction vessel, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the vessel was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reaction vessel was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 90.8% and the selectivity of cyclohexane oxide was 97.0%.

[0057] Example 37 0.1g of the Cu-VN@NC-41 catalyst prepared in Example 4 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 92.0% and the selectivity of cyclohexane oxide was 97.7%.

[0058] Example 38 0.1g of the Cu-VN@NC-42 catalyst prepared in Example 5 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 92.2% and the cyclohexane oxide selectivity was 97.6%.

[0059] Example 39 0.1g of the Cu-VN@NC-43 catalyst prepared in Example 6 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 91.7% and the selectivity of cyclohexane oxide was 97.3%.

[0060] Example 40 0.1 g of the Co-Cu-VN@NC-73 catalyst prepared in Example 15 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 93.0% and the selectivity of cyclohexane oxide was 97.8%.

[0061] Example 41 0.1g of the Cu-VN@NC-51 catalyst prepared in Example 7 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 91.9% and the cyclohexane oxide selectivity was 97.5%.

[0062] Example 42 0.1 g of the Fe-VN@NC-52 catalyst prepared in Example 8 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 90.6% and the selectivity of cyclohexane oxide was 97.1% by chromatography.

[0063] Example 43 0.1g of the Co-VN@NC-53 catalyst prepared in Example 9 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 91.3% and the selectivity of cyclohexane oxide was 97.4%.

[0064] Example 44 0.1 g of the Cu-VN@NC-61 catalyst prepared in Example 10 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 92.1% and the selectivity of cyclohexane oxide was 97.7% by chromatography.

[0065] Example 45 0.1 g of the Fe-VN@NC-62 catalyst prepared in Example 11 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 90.5% and the selectivity of cyclohexane oxide was 96.9%.

[0066] Example 46 0.1g of the Co-VN@NC-63 catalyst prepared in Example 12 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air inside the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 91.1% and the selectivity of cyclohexane oxide was 97.2% by chromatography.

[0067] Example 47 0.1 g of the Cu-VN@NC-71 catalyst prepared in Example 13 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 92.2% and the selectivity of cyclohexane oxide was 97.6% by chromatography.

[0068] Example 48 0.1 g of the Fe-VN@NC-72 catalyst prepared in Example 14 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 90.7% and the selectivity of cyclohexane oxide was 97.0%.

[0069] Example 49 0.1 g of the Cu-VN@NC-81 catalyst prepared in Example 16 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 92.0% and the selectivity of cyclohexane oxide was 97.8% by chromatography.

[0070] Example 50 0.1 g of the Fe-VN@NC-82 catalyst prepared in Example 17 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 90.4% and the selectivity of cyclohexane oxide was 96.8% by chromatography.

[0071] Example 51 0.1 g of the Co-VN@NC-83 catalyst prepared in Example 18 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 91.0% and the selectivity of cyclohexane oxide was 97.1% by chromatography.

[0072] Example 52 0.1 g of the Cu-VN@NC-91 catalyst prepared in Example 19 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen pressure was increased to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 92.3% and the selectivity of cyclohexane oxide was 97.7% by chromatography.

[0073] Example 53 0.1 g of the Fe-VN@NC-92 catalyst prepared in Example 20 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 90.3% and the selectivity of cyclohexane oxide was 96.7% by chromatography.

[0074] Example 54 0.1g of the Co-VN@NC-93 catalyst prepared in Example 21 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 91.2% and the selectivity of cyclohexane oxide was 97.3% by chromatography.

[0075] Example 55 0.1 g of the Cu-VN@NC-101 catalyst prepared in Example 22 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and the cyclohexene conversion rate was 91.8% and the selectivity of cyclohexane oxide was 97.4% by chromatography.

[0076] Example 56 0.1g of the Fe-VN@NC-102 catalyst prepared in Example 23 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 90.2% and the selectivity of cyclohexane oxide was 96.6%.

[0077] Example 57 0.1g of the Co-VN@NC-103 catalyst prepared in Example 24 was weighed into a reactor, followed by the addition of 30g of acetonitrile and 20g of cyclohexene. The air in the reactor was replaced with oxygen three times, and the oxygen was purged to 1.5MPa. The reactor was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 90.9% and the selectivity of cyclohexane oxide was 97.0%.

[0078] Comparative Example 1: Preparation of catalyst Cu-VN@NC-1 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of hot deionized water until completely dissolved, add 1g of melamine (mass ratio 1:5), stir at 80℃ for 12h until the water evaporates; S2-S4: The process and conditions were the same as in Examples 1S2-S4, yielding the catalyst Cu-VN@NC-1. The VN particles in the catalyst exhibited severe agglomeration, with a particle size range of 80-300 nm. FESEM observation revealed no uniformly dispersed VN particles, only large-area clusters and blocky aggregates of VN. The particles were irregularly stacked and exhibited extremely poor dispersibility. AC-HAADF-STEM showed no isolated metallic bright spots or obvious single-atom active sites. The Cu nanoparticles had a particle size of 5-25 nm. Room temperature four-probe conductivity testing showed that the catalyst's conductivity was only 1.6 × 10⁻⁶. -7 With a S / cm ratio, the nitrogen-doped carbon framework has poor electrical conductivity and cannot provide an efficient electron transport pathway for catalytic reactions.

[0079] 0.1 g of the Cu-VN@NC-1 catalyst prepared in Comparative Example 1 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 21.7% and the selectivity of cyclohexane oxide was 37.3%.

[0080] Comparative Example 2: Preparation of the catalyst Cu-VN@NC-2 S1-S3: The process and conditions are the same as in Example 1, except that the S4 pyrolysis step is omitted. The dried solid of S3 is directly used as the catalyst Cu-VN@NC-2. This catalyst has no single-atom dispersed structure, and no isolated metal atoms were observed by AC-HAADF-STEM. The Cu nanoparticles have a particle size of 5-20 nm, and no obvious MN coordination peak is observed by XPS. The conductivity of this catalyst is only 1.8 × 10⁻⁶ at room temperature using a four-probe method. -7 With a S / cm ratio, the nitrogen-doped carbon framework has poor electrical conductivity and cannot provide an efficient electron transport pathway for catalytic reactions.

[0081] 0.1 g of the Cu-VN@NC-2 catalyst prepared in Comparative Example 2 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 23.6% and the selectivity of cyclohexane oxide was 27.3%.

[0082] Comparative Example 3: Preparation of the catalyst Cu-VN@NC-3 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 85℃ deionized water until completely dissolved, add 1.6g of melamine, and stir at 80℃ for 12h until the water evaporates; S2-S4: The process and conditions are the same as in Example 1 S2-S4, and the catalyst Cu-VN@NC-3 is obtained. XPS test shows that the N element content is only 0.5wt%.

[0083] 0.1 g of Cu-VN@NC-3 catalyst prepared in Comparative Example 3 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 14.8% and the cyclohexane oxide selectivity was 19.2%.

[0084] Comparative Example 4: Preparation of the catalyst Cu-VN@NC-4 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 85℃ deionized water until completely dissolved, add 9g of melamine, and stir at 80℃ for 12h until the water evaporates; S2-S4: The process and conditions are the same as in Example 1 S2-S4, and the catalyst Cu-VN@NC-4 is obtained. The carbon skeleton is over-coated with VN particles. EDS surface scan shows that the distribution of V, N and C elements is uneven, which hinders the transfer of NV electrons and the active sites are masked.

[0085] 0.1 g of the Cu-VN@NC-4 catalyst prepared in Comparative Example 4 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 21.3% and the selectivity of cyclohexane oxide was 19.9%.

[0086] Comparative Example 5: Preparation of the catalyst Cu-VN@NC-5 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 65℃ deionized water until completely dissolved, add 4g of melamine, and stir at 65℃ for 12h until the water evaporates; S2-S4: The process and conditions were the same as in Examples 1S2-S4, yielding the catalyst Cu-VN@NC-5. The excessively low temperature resulted in slow moisture evaporation, localized melamine precipitation, and uneven material mixing. FESEM observation showed that the VN particles had a diameter of 200-400 nm, with uneven particle size distribution and obvious agglomeration. EDS surface scan analysis showed uneven distribution and significant enrichment of V, N, and C elements.

[0087] 0.1 g of Cu-VN@NC-5 catalyst prepared in Comparative Example 5 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 12.4% and the selectivity of cyclohexane oxide was 29.9%.

[0088] Comparative Example 6: Preparation of the catalyst Cu-VN@NC-6 S1: Dissolve 0.2g of ammonium metavanadate in 50mL of 85℃ deionized water until completely dissolved, add 4g of melamine, and stir at 80℃ for 8h until the water evaporates; S2-S4: The process and conditions were the same as in Example 1 S2-S4, yielding the catalyst Cu-VN@NC-6. Insufficient stirring time resulted in incomplete mixing of the materials, leading to an uneven support structure after calcination. FESEM observation showed that the VN particles had a diameter of 10-200 nm, with uneven particle size distribution and obvious agglomeration. EDS surface scan analysis showed uneven distribution and significant enrichment of V, N, and C elements. Nitrogen adsorption-desorption (BET) analysis revealed a specific surface area of ​​26.8 m². 2 / g, the carrier's pore structure is underdeveloped.

[0089] 0.1 g of Cu-VN@NC-6 catalyst prepared in Comparative Example 6 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air inside the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 23.2% and the selectivity of cyclohexane oxide was 18.7%.

[0090] Comparative Example 7: Preparation of the catalyst Cu-VN@NC-7 S1: The process and conditions are the same as S1 in Example 1; S2: After grinding the powder to a particle size of less than 50μm, the temperature was increased to 450℃ in a tube furnace under nitrogen atmosphere at 5℃ / min, and calcined for 3h to obtain VN@NC carrier; S3-S4: The process and conditions were the same as S3-S4 in Example 1, yielding the catalyst Cu-VN@NC-7. The calcination temperature was too low, the precursor was not completely decomposed, no VN phase was formed, and XRD showed no VN characteristic peaks, resulting only in amorphous carbon material.

[0091] 0.1 g of Cu-VN@NC-7 catalyst prepared in Comparative Example 7 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 21.2% and the selectivity of cyclohexane oxide was 17.9%.

[0092] Comparative Example 8: Preparation of the catalyst Cu-VN@NC-8 S1: The process and conditions are the same as S1 in Example 1; S2: After grinding the powder to a particle size of less than or equal to 50 μm, the temperature was increased to 550℃ in a tube furnace under nitrogen atmosphere at 15℃ / min, and calcined for 3h to obtain VN@NC carrier; S3-S4: The process and conditions are the same as S3-S4 in Example 1, and the catalyst Cu-VN@NC-8 is obtained. The rapid heating leads to local overheating, VN particles agglomerate, and FESEM observation shows that the NC skeleton is cracked and the support structure is destroyed.

[0093] 0.1 g of the Cu-VN@NC-8 catalyst prepared in Comparative Example 8 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 35.2% and the selectivity of cyclohexane oxide was 43.2%.

[0094] Comparative Example 9: Preparation of catalyst Zn-VN@NC-9 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 120μL of 100mg / mL zinc nitrate aqueous solution, sonicate for 30min, stir at room temperature for 7h, centrifuge and wash, and then vacuum dry at 70℃ for 14h. S4: The process and conditions are the same as in S4 of Example 1, to obtain the catalyst Zn-VN@NC-9.

[0095] 0.1 g of the Zn-VN@NC-9 catalyst prepared in Comparative Example 9 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 10.3% and the selectivity of cyclohexane oxide was 30.2%.

[0096] Comparative Example 10: Preparation of catalyst Ni-VN@NC-10 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 120μL of 100mg / mL nickel nitrate aqueous solution, sonicate for 30min, stir at room temperature for 7h, centrifuge and wash, and then vacuum dry at 70℃ for 14h. S4: The process and conditions were the same as in S4 of Example 1, yielding the catalyst Ni-VN@NC-10. Clear Ni nanoparticles were visible under AC-HAADF-STEM, but no single-atom active sites could be formed.

[0097] 0.1 g of the Ni-VN@NC-10 catalyst prepared in Comparative Example 10 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air inside the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 43.8% and the selectivity of cyclohexane oxide was 19.6%.

[0098] Comparative Example 11: Preparation of the catalyst Cu-VN@NC-11 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 50μL of 100mg / mL copper nitrate aqueous solution, sonicate for 30min, stir at room temperature for 7h, centrifuge and wash, and then vacuum dry at 70℃ for 14h. S4: The process and conditions are the same as S4 in Example 1, and the catalyst Cu-VN@NC-11 is obtained. The Cu loading is only 0.3 wt% according to ICP test.

[0099] 0.1 g of Cu-VN@NC-11 catalyst prepared in Comparative Example 11 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 46.2% and the selectivity of cyclohexane oxide was 39.8%.

[0100] Comparative Example 12: Preparation of the catalyst Cu-VN@NC-12 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 625μL of 100mg / mL copper nitrate aqueous solution, sonicate for 30min, stir at room temperature for 7h, centrifuge and wash, and then vacuum dry at 70℃ for 14h. S4: The process and conditions are the same as S4 in Example 1, and the catalyst Cu-VN@NC-12 is obtained. Cu nanoparticles are observed to be atom-aggregated by AC-HAADF-STEM.

[0101] 0.1 g of Cu-VN@NC-12 catalyst prepared in Comparative Example 12 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 69.7% and the selectivity of cyclohexane oxide was 32.1%.

[0102] Comparative Example 13: Preparation of the catalyst Cu-VN@NC-13 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 120μL of 100mg / mL copper nitrate aqueous solution, sonicate for 30min, stir at room temperature for 4h, centrifuge and wash, and then vacuum dry at 70℃ for 12h. S4: The process and conditions were the same as in S4 of Example 1, and the catalyst Cu-VN@NC-13 was obtained. Due to insufficient stirring time, the adsorption of metal salt was uneven. Cu nanoparticles were observed to be atom-gathered by AC-HAADF-STEM.

[0103] 0.1 g of Cu-VN@NC-13 catalyst prepared in Comparative Example 13 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 46.2% and the selectivity of cyclohexane oxide was 40.7%.

[0104] Comparative Example 14: Preparation of the catalyst Cu-VN@NC-14 S1-S2: The process and conditions are the same as S1-S2 in Example 1; S3: Take 0.6g of VN@NC and place it in 12mL of methanol for ultrasonic dispersion. Add 120μL of 100mg / mL copper nitrate aqueous solution, sonicate for 30min, stir at room temperature for 4h, centrifuge and wash, and then vacuum dry at 1200℃ for 12h. S4: The process and conditions were the same as in S4 of Example 1, yielding the catalyst Cu-VN@NC-14. Due to excessively high drying temperature, the carbon skeleton of the support shrank, causing the pore structure to collapse. Nitrogen adsorption-desorption (BET) analysis revealed a support specific surface area of ​​only 70.2 m². 2 / g, the carrier's pore structure is underdeveloped.

[0105] 0.1 g of Cu-VN@NC-14 catalyst prepared in Comparative Example 14 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 30.8% and the selectivity of cyclohexane oxide was 44.5%.

[0106] Comparative Example 15: Preparation of the catalyst Cu-VN@NC-15 S1-S3: The process and conditions are the same as in Example 1 S1-S3; S4: The obtained solid was heated to 750℃ at a rate of 5℃ / min and pyrolyzed for 2 hours in an argon atmosphere to obtain the catalyst Cu-VN@NC-15. If the pyrolysis temperature is too low, a stable coordination structure cannot be formed. XPS analysis showed that the metal exists in ionic form, which is easily lost and has poor stability.

[0107] 0.1 g of the Cu-VN@NC-15 catalyst prepared in Comparative Example 15 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air inside the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion was 72.6% and the cyclohexane oxide selectivity was 73.4%. After the catalyst was recycled once, the cyclohexene conversion was measured to be 12.8% and the cyclohexane oxide selectivity was 19.7%.

[0108] Comparative Example 16: Preparation of the catalyst Cu-VN@NC-16 S1-S3: The process and conditions are the same as in Example 1 S1-S3; S4: The obtained solid was pyrolyzed at 950℃ in an argon atmosphere at a rate of 5℃ / min for 6 hours to obtain the catalyst Cu-VN@NC-16. Excessive pyrolysis time led to over-graphitization of the carbon framework, resulting in a support specific surface area of ​​only 58.3 m², as determined by nitrogen adsorption-desorption (BET) analysis. 2 / g.

[0109] 0.1 g of Cu-VN@NC-16 catalyst prepared in Comparative Example 16 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was 43.2% and the selectivity of cyclohexane oxide was 59.3%.

[0110] Comparative Example 17 0.08 g of the Cu-VN@NC catalyst (catalyst: cyclohexene = 1:250) prepared in Example 1 was weighed into a reactor, followed by the addition of 30 g of acetonitrile and 20 g of cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The reactor was then sealed and stirred at 60 °C for 3 h. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the cyclohexene conversion rate was only 65.2%, indicating that the reaction was not complete.

[0111] Comparative Example 18 0.1g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reaction vessel, followed by the addition of 10g acetonitrile and 20g cyclohexene. The air in the vessel was replaced three times, and oxygen was introduced to 1.5MPa. The reaction vessel was then sealed and stirred at 60°C for 3 hours. After the reaction was completed, the reaction solution was filtered, and chromatographic analysis showed that the selectivity of cyclohexane oxide was only 82.5%, with the ring-opening byproduct cyclohexanediol being generated.

[0112] Comparative Example 19 Weigh 0.1g of the Cu-VN@NC catalyst prepared in Example 1 into a reactor, then add 30g of water and 20g of cyclohexene, replace the air in the reactor three times, purge with oxygen to 1.5MPa, seal the reactor, and stir at 60°C for 3h; the reaction system separates into layers, the cyclohexene conversion rate is only 18.5%, and almost no target product cyclohexane oxide is generated.

[0113] Comparative Example 20 Weigh 0.1g of the Cu-VN@NC catalyst prepared in Example 1 into a reactor, then add 30g of butyl acetate and 20g of cyclohexene, replace the air in the reactor three times, purge with oxygen to 1.5MPa, seal the reactor, and stir at 60°C for 3h; the cyclohexene conversion rate is 45.3%, and the selectivity of cyclohexane oxide is 72.1%.

[0114] Comparative Example 21 0.1g of the Cu-VN@NC catalyst prepared in Example 1 was weighed into a reactor, followed by the addition of 30g acetonitrile and 20g cyclohexene (solvent:cyclohexene = 1.5:1). The air in the reactor was replaced three times, and oxygen was introduced to 0.3MPa. The reactor was then sealed and stirred at 60°C for 3 hours. Due to insufficient oxygen partial pressure, the oxidation reaction was incomplete, and the cyclohexene conversion rate was only 52.7%, with a large amount of raw materials remaining unreacted.

[0115] Comparative Example 22 Weigh 0.1g of the Cu-VN@NC catalyst prepared in Example 1 into a reactor, then add 30g of acetonitrile and 20g of cyclohexene (solvent: cyclohexene = 1.5:1), replace the air in the reactor three times, purge with oxygen to 1.5MPa, seal the reactor, and stir at 85℃ for 3h; excessive temperature causes the cyclohexane oxide to decompose by ring opening, with a selectivity of only 68.5%, and the byproducts are cyclohexanediol and cyclohexanone.

[0116] Comparative Example 23 S1: Without adding ammonium metavanadate, dissolve 6g of melamine in 60mL of 90℃ deionized water until completely dissolved, and stir at 90℃ for 14h until the water evaporates; The S2-S4 process and conditions are the same as in Example 1 S2-S4, yielding the Cu-NC catalyst.

[0117] 0.1 g of Cu-NC catalyst was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air inside the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The mixture was stirred at 60 °C for 3 hours. After the reaction, the reaction solution was filtered, and the oil phase was analyzed by chromatography. The cyclohexene conversion rate was found to be 42.3%, and the selectivity for cyclohexane oxide was 37.8%. There was no synergistic effect between VN and NC, indicating poor activity and selectivity.

[0118] Comparative Example 24: Preparation of the catalyst Cu-VN@NC-16 S1: 0.3g of ammonium metavanadate and 6g of melamine are directly physically mixed to obtain powder without going through the aqueous solution dissolution and evaporation steps; The S2-S4 process and conditions are the same as those in Example 1, yielding the catalyst Cu-VN@NC-16.

[0119] 0.1 g of the Cu-VN@NC-16 catalyst prepared in Comparative Example 24 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air inside the reactor was purged three times, and oxygen was introduced to a pressure of 1.5 MPa. The mixture was stirred at 60 °C for 3 hours. After the reaction, the reaction solution was filtered, and the oil phase was analyzed by chromatography. The cyclohexene conversion rate was found to be 55.6%, and the selectivity for cyclohexane oxide was 47.9%.

[0120] Comparative Example 25: Preparation of the catalyst Cu-urea-NC S1: Dissolve 0.3g ammonium metavanadate and 6g urea in 60mL of 90℃ deionized water, and stir at 90℃ for 14h until the water evaporates; S2-S4: The process and conditions are the same as S2-S4 in Example 1, to obtain the catalyst Cu-urea-NC.

[0121] 0.1 g of the Cu-urea-NC catalyst prepared in Comparative Example 25 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air inside the reactor was replaced three times, and oxygen was introduced to 1.5 MPa. The mixture was stirred at 60 °C for 3 hours. After the reaction, the reaction solution was filtered, and the oil phase was analyzed by chromatography. The cyclohexene conversion was found to be 17.5%, and the selectivity for cyclohexane oxide was 22.4%.

[0122] Comparative Example 26: Preparation of the catalyst Cu-dicyandiamide-NC S1: Replace melamine with dicyandiamide. Dissolve 0.3g ammonium metavanadate and 6g dicyandiamide in 60mL of 90℃ deionized water and stir at 90℃ for 14h until the water evaporates. S2-S4: The process and conditions are the same as in Example 1 S2-S4, to obtain the catalyst Cu-dicyandiamide-NC.

[0123] 0.1 g of the Cu-dicyandiamide-NC catalyst prepared in Comparative Example 26 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air inside the reactor was replaced three times, and oxygen was introduced to a pressure of 1.5 MPa. The mixture was stirred at 60 °C for 3 hours. After the reaction, the reaction solution was filtered, and the oil phase was analyzed by chromatography. The cyclohexene conversion was found to be 38.2%, and the selectivity for cyclohexane oxide was 56.7%.

[0124] Comparative Example 27: Preparation of the catalyst Cu-ammonium chloride-VN@NC S1: Dissolve 0.3g of ammonium metavanadate in 60mL of 90℃ deionized water until completely dissolved, add 6g of melamine and 1.5g of ammonium chloride, stir at 90℃ for 14h until the water evaporates; S2-S4: The process and conditions are the same as in Example 1 S2-S4, to obtain the catalyst Cu-ammonium chloride-VN@NC.

[0125] 0.1 g of the Cu-ammonium chloride-VN@NC catalyst prepared in Comparative Example 27 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air in the reactor was replaced three times, and oxygen was introduced to a pressure of 1.5 MPa. The mixture was stirred at 60 °C for 3 hours. After the reaction, the reaction solution was filtered, and the oil phase was analyzed by chromatography. The cyclohexene conversion was found to be 29.6%, and the selectivity for cyclohexane oxide was 33.8%.

[0126] Comparative Example 28: In-situ nitrogen-doped catalyst Cu-C-NH3 in ammonia water S1: Dissolve 0.3g of ammonium metavanadate in 60mL of 90℃ deionized water until completely dissolved, add 6g of glucose and 1.5g of ammonia water, stir at 90℃ for 14h until the water evaporates; S2-S4: The process and conditions are the same as in Example 1 S2-S4, to obtain the Cu-C-NH3 catalyst.

[0127] 0.1 g of the Cu-C-NH3 catalyst prepared in Comparative Example 28 was weighed into a reactor, followed by the addition of 30 g acetonitrile and 20 g cyclohexene. The air inside the reactor was replaced three times, and oxygen was introduced to a pressure of 1.5 MPa. The mixture was stirred at 60 °C for 3 hours. After the reaction, the reaction solution was filtered, and the oil phase was analyzed by chromatography. The cyclohexene conversion was found to be 22.8%, and the selectivity for cyclohexane oxide was 27.6%.

Claims

1. The application of a single-atom nitrogen-doped carbon catalyst in the catalytic epoxidation of cyclohexene to prepare cyclohexane oxide, characterized in that: Includes the following steps: S1: Dissolve ammonium metavanadate in hot water at 80~95℃ to obtain a solution; add melamine to the obtained solution and stir at 70~100℃ to evaporate the water and obtain powder; the mass ratio of ammonium metavanadate to melamine is 1:10~1:

40. S2: Collect the powder obtained in step S1, grind it to make the powder particle size less than or equal to 50 micrometers, and calcine it at 500~600℃ for 2~6 hours to obtain nitrogen-doped carbon material VN@NC carrier. S3: Weigh the above nitrogen-doped carbon material and disperse it in methanol and / or aqueous solution. Add an aqueous solution of metal salt, disperse, and stir at room temperature. Centrifuge to obtain a solid, wash and dry it. S4: Weigh the solid obtained in step S3 and pyrolyze it at 800~1000℃ in an inert atmosphere for 1~5 hours to obtain a single-atom nitrogen-doped carbon catalyst. The stirring time in step S1 is 10-20 hours; In step S2, the heating rate from room temperature to calcination temperature is 2~10℃ / min, and the atmosphere is an inert atmosphere.

2. The application according to claim 1, characterized in that: In step S3, the concentration of the nitrogen-doped carbon material in methanol and / or aqueous solution is 0.01-0.2 g / mL; The concentration of the metal salt aqueous solution is 100~120 mg / mL; The metal salt is one or more of copper nitrate, copper chloride, ferric nitrate, ferric chloride, cobalt nitrate, and cobalt chloride; The mass ratio of metal salt to VN@NC carrier is 1:100 to 1:10; The stirring time is 5-10 hours, the drying temperature is 60-90℃, and the drying time is 10-24 hours. The dispersion is achieved by ultrasonic dispersion.

3. The application according to claim 1, characterized in that: In step S4, the heating rate from room temperature to the pyrolysis temperature is 2~10℃ / min, and the inert atmosphere is nitrogen and / or argon.

4. The application according to claim 1, characterized in that: The reaction is carried out in a reaction vessel by adding the single-atom nitrogen-doped carbon catalyst, solvent, and reactant cyclohexene to the reaction vessel, replacing the air in the vessel with oxygen, filling the vessel with oxygen to the reaction pressure, and completing the epoxidation reaction at the reaction temperature to obtain the cyclohexane oxide.

5. The application according to claim 4, characterized in that: The mass ratio of catalyst to cyclohexene is 1:200 to 1:100, and the mass ratio of solvent to cyclohexene is 1:1 to 2:

1.

6. The application according to claim 4, characterized in that: The solvent is one or more of acetonitrile, dichloromethane, dichloroethane, ethanol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and 1,4-dioxane.

7. The application according to claim 4, characterized in that: The reaction pressure is 0.5~2MPa, the reaction temperature is 50~80℃, and the reaction time is 2~5 hours.

Citation Information

Patent Citations

  • Method for preparing keto ester from hydroxyl ester through catalytic oxidation

    CN110183327A

  • Preparation method of lithium / zinc ion battery electrode material vanadium nitride@nitrogen-doped carbon

    CN113206244A

  • Method for preparing cyclohexene oxide by cyclohexene oxidation

    CN114456127A